Coxsackievirus B3 replication and pathogenesis. (April 2015) - Garmaroudi, Farshid S; Marchant, David; Hendry, Reid; Luo, Honglin; Yang, Decheng; Ye, Xin; Shi, Junyan; McManus, Bruce M
ABSTRACT : Viruses such as coxsackievirus B3 (CVB3) are entirely host cell-dependent parasites. Indeed, they must cleverly exploit various compartments of host cells to complete their life cycle, and consequently launch disease. Evolution has equipped this pico-rna-virus, CVB3, to use different strategies, including CVB3-induced direct damage to host cells followed by a host inflammatory response to CVB3 infection, and cell death to super-additively promote target organ tissue injury, and dysfunction. In this update, the patho-stratagems of CVB3 are explored from molecular, and systems-level approaches. In summarizing recent developments in this field, we focus particularly on mechanisms by which CVB3 can harness different host cell processes including kinases, host cell-killing and cell-eating machineries, matrix metalloproteinases and miRNAs to promote disease.